On the First Curve in the FučiK Spectrum with Weights for a Mixed p-Laplacian - Liamidi Leadi; Aboubacar Marcos (International Journal of Mathematics and Mathematical Sciences)
We show the existence of a first curve in the Fučik spectrum with weights for the p-Laplacian under mixed boundary conditions. We also study the asymptotic behavior of this first curve.